(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study examined accounting skills as predictors of entrepreneurial intentions among university graduates in Southwest of Nigeria. Two research questions guided the study. A descriptive survey research design was used. The population of the study was 281 Business Education Postgraduate Students in State owned Universities in Southwest. Since the population of the study was not too large, there was no need for sampling. The study used adapted researcher self-developed questionnaire titled: Accounting Skills and Entrepreneurial Intentions Questionnaire (SASEIQ) for data collection with (r = .88) as reliability coefficient. Mean, standard deviation and bar-chart were adopted for answering and presenting research question 1. Research question 2 was analyzed using PPMC. The findings of the study indicated that critical, attention, time management, financial reporting, business knowledge, software proficiency, budgeting, analytic reason, taxation, accuracy and precision, standard accounting and communication skills were the needed accounting skills for entrepreneurial intentions among university graduates in Southwest of Nigeria. There was a positive relationship between accounting skills (r = .221, p < .05) and entrepreneurial intentions among university graduates in Southwest of Nigeria. It was recommended that professional and highly educated person in accounting should be employed to teach students accounting with the view to deliver the needed accounting skills for students. The university authority should made available entrepreneurial village in university environment to expand students’ knowledge on the intrigues of entrepreneurial intentions for their future sustainability.